2018
DOI: 10.1080/00480169.2017.1416693
|View full text |Cite
|
Sign up to set email alerts
|

Ergovaline does not alter the severity of ryegrass staggers induced by lolitrem B

Abstract: There was no evidence for ergovaline increasing the severity of ryegrass staggers induced by lolitrem B. In situations where the severity of ryegrass staggers appears to be greater than that predicted on the basis of concentrations of lolitrem B, the presence of other tremorgenic alkaloids should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The possibility also exists of a synergistic effect between the two toxin classes. In some New Zealand studies, there is the suggestion of ergovaline exacerbating ryegrass staggers (Fletcher and Easton 1997) while in others there has been no evidence for a synergistic effect of ergovaline to increase the effects of lolitrem B (Finch et al 2018). In Australia, occasional severe perennial ryegrass toxicity (PRGT) is observed in sheep and Reed et al (2016) concluded that the ingestion of ergot alkaloids combined with the impact of high solar radiation on the animals' heat load are important factors in this unusually severe form of ryegrass toxicity.…”
Section: Effects Of Ergovaline Identified In New Zealandmentioning
confidence: 99%
“…The possibility also exists of a synergistic effect between the two toxin classes. In some New Zealand studies, there is the suggestion of ergovaline exacerbating ryegrass staggers (Fletcher and Easton 1997) while in others there has been no evidence for a synergistic effect of ergovaline to increase the effects of lolitrem B (Finch et al 2018). In Australia, occasional severe perennial ryegrass toxicity (PRGT) is observed in sheep and Reed et al (2016) concluded that the ingestion of ergot alkaloids combined with the impact of high solar radiation on the animals' heat load are important factors in this unusually severe form of ryegrass toxicity.…”
Section: Effects Of Ergovaline Identified In New Zealandmentioning
confidence: 99%
“…In previous studies of active metabolites produced by Epichloë endophytes, only alkaloids have been proven to protect hosts from herbivory. Four types of alkaloids have been reported: ergot alkaloids, indole-diterpene alkaloids (such as lolitrem B), lolines and peramine, all of which have anti-insect activity, and the first two types can cause poisoning in livestock [ 20 , 21 , 22 , 23 , 24 , 25 ]. The kinds of alkaloids produced in different grass–endophyte symbionts vary with the species of fungal endophytes; for example, Epichloë festucae var.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the naturally occurring E. coenophiala strains produce alkaloids of various classes-namely lolines, peramine, indole-diterpenes, and ergot alkaloidsof which some ergot alkaloids and some indole-diterpenes are toxic to mammals (Bacon et al, 1977;Bacon, 1995;Finch et al, 2018;McLeay et al, 1999;Takach and Young, 2014). Although it is feasible to eliminate the endophyte, because tall fescue does not require it to grow, it has been demonstrated that tall fescue lacking E. coenophiala does not persist as well as plants that harbor the endophyte (Bouton et al, 1993).…”
mentioning
confidence: 99%